ERECTILE DYSFUNCTION IN HAEMODIALYSIS PATIENTS IN AL-IMAMAIN AL-KADHIMIAN MEDICAL CITY AND AL-KINDY TEACHING HOSPITALS (Iraqi Journal of Medical Sciences, 2016)
Background:Erectile dysfunction is the inability to attain or maintain an erection sufficient for satisfactory sexual performance. There is a very high prevalence among dialysis patients. Many factors play a role including the disease itself and dialysis.Objective:To identify the rate of erectile dysfunction in uremic patient undergoing haemodialysis and to find the association between the erectile dysfunction and many confounding factors.Methods: All male patients of end stage renal disease were kept on maintenance haemodialysis therapy. Patients were divided into two groups according to the International index of erectile function-5, first group with erectile dysfunction with score of 21 and less, the second group without erectile dysfunction with score of 22 and more.Results:The percentage of erectile dysfunction in the study sample was (84.9%). Factors responsible for erectile dysfunction are diabetes mellitus (73.3%), increasing age (75.5%) of patients, high predialysis urea level (82.2%), smoking, hepatitis B and C virus infection, systolic blood pressure, albumin, creatinine, haemoglobin and the duration of dialysis are not related.Conclusion:Majority of the patients with end stage renal disease on maintenance haemodialysis have higher rate of erectile dysfunction. Major factors responsible for erectile dysfunction are diabetes mellitus, increasing age and high predialysis urea.Keywords: Haemodialysis, erectile dysfunction, International index of erectile function-5.
Keywords: Haemodialysis; erectile dysfunction; International index of erectile function5